Pengaruh Model Pembelajaran Firework Terhadap Pembentukan Karakter Siswa di SMP Nurul Huda - Baiq Kartika Agustina; Sapka Mawarzani; Marazaenal Adipta (Tirai Edukasi : Jurnal Pendidikan, 2026)
This study aims to analyze the influence of the firework learning model on character building among students of SMP Nurul Huda Menemeng. The model was chosen due to its emphasis on collaboration, creativity, and responsibility in the learning process. The research employed a quasi-experimental design with two groups: an experimental class using the firework model and a control class applying conventional methods. The research instruments consisted of a student character questionnaire and learning achievement tests. Data analysis used a t-test to compare the results between the two groups. The findings revealed a significant difference between the experimental and control groups, where the experimental group showed better improvement in cooperation, responsibility, self-confidence, and learning motivation. These results suggest that the firework learning model can serve as an effective alternative in social studies learning to support character education goals